Interkulturele probleme in beeldkommunikasie - Pieter Jacobus Fourie (Communicare)
This paper focuses on only three of the many aspects of intercultural communication which are relevant to pictorial communication. (i) Stereotyping and the one-sided view which is created by one cultural and/or ethnic group of another; (ii) the misconception of the picture as universal language; (iii) the acknowledge ment of heterogeneity within a specific cultural and/or ethnic group and the consequent necessity to plan the media supply in accordance with the variety of different cultural tastes within a society. What is said, is that this paper must be seen as an introduction. Neither time nor space allows for a more intensive look at the theoretical principles on which the study of these three aspects or problems are based. Before these three aspects are discussed, a synopsis is given of the status of entertainment in the mass media and the model function of film through which it becomes a socialising and ideologizing instrument.